Watershed Modelling Using Control System Concept. (2016) - Aswathy, S.; Sajikumar, N.; Mehsa, M.
Abstract: Watershed modelling is an essential component for water resources management. Surface hydrologic response in a watershed can be thought as a combination of routing elements and runoff production units. This study develops a watershed model using control system concept in MATLAB Simulink module. It is built as a combination of routing elements and runoff production units. Routing is carried out by using non-linear form of Muskingum method whereas runoff generation is by means of linear/non-linear reservoirs. The developed model is tested for four events which are selected such that there exits extreme flows. The performance of non-linear model was slightly better than that of linear model. Though the simulated and observed discharges follow the same trend, there exists discrepancy between simulated and measured flows which indicates the need for further improvement in the model.